Diastereo- and enantioselective [3 + 3] cycloaddition of spirocyclopropyl oxindoles using both aldonitrones and ketonitrones - Peng-Wei Xu (Nature Portfolio, 2017)
Chiral spirocyclic compounds are important structural motifs for drug discovery. Here, the authors report a synthetic route to spirocycles based on enantioselective cycloaddition of activated spirocyclopropyl oxindoles, which act as donor-acceptor cyclopropanes.